Perceptions of college students in consuming whole grain foods made with Brewers' Spent Grain. Issue 1 (29th November 2018) - Combest, Shannon; Warren, Cynthia
Abstract: One‐third of all food produced for human consumption is wasted producing landfill accumulation and greenhouse gas emissions. Brewers' Spent Grains (BSGs) are the leftover grains from beer production, and each year approximately 30 million tons of BSG is generated globally by the brewing industry. Reclaiming BSG as a potential human food source is an opportunity for reducing food waste in the food supply chain. Six focus groups were conducted using 37 college students to determine their consumption of whole grains, perceptions of whole grains versus refined grains, and interest in or barriers related to consuming and purchasing foods made with BSG. Focus groups were transcribed verbatim and analyzed using constant comparative analysis to identify themes and discover relationships among the study aims. Thirteen themes emerged from focus group discussions with Concept of Health, Sensory, and Experience with BSG representing the top three discussed. Participants believed whole grains are healthier and contain more nutrients than refined grains. Most participants enjoyed the BSG foods provided; however, some noted a darker appearance and lingering fiber particles or aftertaste. Findings indicate participants who are hereditary whole grain consumers are acculturated to whole grain sensory attributes and nutritional benefits and would be more receptive to consuming BSG foods in future studies. We concluded most focus group participants were open to tasting BSG foods, but hereditary whole grain consumers should be the target consumer audience, and educating consumers on sensory attributes, potential health benefits, and environmental benefits is necessary to overcome the barriers associated with BSG. Abstract : Reclaiming Brewers' Spent Grains (BSG), the leftover grains from beer production, as a potential human food source is an opportunity for reducing food waste. Six focus groups were conducted using 37 college students to determine their consumption of whole grains, perceptions of whole grains versus refined grains and interest in or barriers related to consuming and purchasing foods made with BSG. Thirteen themes emerged from focus group discussions, and we concluded most participants were open to tasting BSG foods; however, consumers need further education on BSG sensory attributes.